Sistem Pengambilan Keputusan Penentuan Siswa Berprestasi SD Negeri Daha Walu dengan Metode Weighted Product - Murtiati Endang Ina; Cecilia Dai Payon Binti Gabriel; Felysitas Ema Ose Sanga (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
Students who excel academically as well as non-academically in the classroom and at school. High achieving students are very difficult to find because there is no system that can assess student talent in the classroom. Thus, there is a need for a computer-based system that can facilitate teachers in identifying outstanding students. . The system is an application that is made, SPK using the WP method. With the application of the following method, the best option can be determined from various choices and their features through the weighing process. Thus, the results of this research can help teachers and principals at SDN Daha Walu in obtaining the highest score ranking based on the system that can be used as a reference for decision making.